Special elements and values needed in leadership for special education - Mosbiran, Nor Fauziyana; Mustafa, Mohamad Zaid; Nordin, Mohd Norazmi (2021)
Educational leadership is very important in determining the success of an educational organization, especially in schools. Effective leadership is more needed when it involves more challenging and diverse situations such as in special education. Many competent school leaders have succeeded in making the school organizations they lead as successful. Nevertheless, the same leaders are seen to be less effective on leadership in special education. Therefore, this study was conducted to explore the elements and added value that a leader must have to lead special education effectively. This qualitative study was conducted by involving an interview session with 20 special education teachers in the state of Johor, Malaysia. Their perceptions and opinions are analyzed to obtain the relevant elements and added value. As a result of the thematic analysis conducted, there are five additional elements that need to be practiced by special education leaders in schools in each situation, namely loving, caring, sensitive, friendly and cooperative network. These five elements were agreed upon by the respondents involved and should be given attention in every decision made by leaders in special education. It is hoped that the findings of this study can help special education leaders in schools to practice effective leadership and in turn lead the continued success of special education.